Comparative analysis of SARS‐CoV‐2 Omicron BA.2.12.1 and BA.5.2 variants. Issue 1 (28th November 2022) - Ong, Chon Phin; Ye, Zi‐Wei; Tang, Kaiming; Liang, Ronghui; Xie, Yubin; Zhang, Hongzhuo; Qin, Zhenzhi; Sun, Haoran; Wang, Tong‐Yun; Cheng, Yun; Chu, Hin; Chan, Jasper F.‐W.; et al.
Abstract: The initial severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) Omicron subvariants, BA.1 and BA.2, are being progressively displaced by BA.5 in many countries. To provide insight on the replacement of BA.2 by BA.5 as the dominant SARS‐CoV‐2 variant, we performed a comparative analysis of Omicron BA.2.12.1 and BA.5.2 variants in cell culture and hamster models. We found that BA.5.2 exhibited enhanced replicative kinetics over BA.2.12.1 in vitro and in vivo, which is evidenced by the dominant BA.5.2 viral genome detected at different time points, regardless of immune selection pressure with vaccine‐induced serum antibodies. Utilizing reverse genetics, we constructed a mutant SARS‐CoV‐2 carrying spike F486V substitution, which is an uncharacterized mutation that concurrently discriminates Omicron BA.5.2 from BA.2.12.1 variant. We noticed that the 486th residue does not confer viral replication advantage to the virus. We also found that 486V displayed generally reduced immune evasion capacity when compared with its predecessor, 486F. However, the surge of fitness in BA.5.2 over BA.2.12.1 was not due to stand‐alone F486V substitution but as a result of the combination of multiple mutations. Our study upholds the urgency for continuous monitoring of SARS‐CoV‐2 Omicron variants with enhanced replication fitness.